2022
DOI: 10.21009/jep.v13i2.27159
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Program Tahfiz Qur’an Di MTSN 5 Agam: Pendekatan Evaluasi Program Pendidikan Metode Cippo

Abstract: Penelitian ini bertujuan untuk mengevaluasi pelaksanaan program sekolah MTsN 5 Agam yaitu ProgramTahfidz Qur’an sebagai salah satu Mata Pelajar muatan wajib disekialh tersebut. Penenlitian ini menganalisis program pendidikan MTsN 5 Agam dengan menggunakan model evaluasi CIPPO ((komponen konteks (C), masukan atau Input (I), Proses (P), dan hasil atau produk (P), juga diperlukan evaluasi terhadap dampak atau outcome (O)). Penelitian ini merupakan jenis penelitian kualitatif, kemudahan menggunakan jenis penelitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
1
Order By: Relevance
“…The implementation of audit policies in districts/cities in Indonesia still found obstacles including sharp downwards blunt upwards, inadequate costs and infrastructure, unavailability of death forms, unavailable SOPs, attitude of executors who ignore orders, and the difficulty of maintaining the confidentiality of AMP 12,13,14,15,16 . Based on the preliminary study it was found that the Implementation of the Maternal Perinatal Surveillance and Response (AMP-SR) Audit in Semarang City had been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of audit policies in districts/cities in Indonesia still found obstacles including sharp downwards blunt upwards, inadequate costs and infrastructure, unavailability of death forms, unavailable SOPs, attitude of executors who ignore orders, and the difficulty of maintaining the confidentiality of AMP 12,13,14,15,16 . Based on the preliminary study it was found that the Implementation of the Maternal Perinatal Surveillance and Response (AMP-SR) Audit in Semarang City had been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Oleh sebab itu, program peningkatan kompetensi membaca al-Qur'an bagi siswa perlu digalakkan (Wahyuni & Aisyah, 2020). (Fahmi et al, 2022). Kedua, Pita Saliya, Kris Setyaningsih, dan Rabial Kanada dalam penelitiannya menjelaskan bahwa evaluasi program Tahfiz Qur'an di Pondok Pesantren Baitul Qur'an menunjukkan hasil yang sangat baik.…”
unclassified